Kontribusi Reformis Pendidikan Swiss Abad ke-18: Johan Heinrich Pestalozzi - Irfan Wahyu Prananto; Helda Kusuma Wardani (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2023)
Pestalozzi was a Swiss 18th-century education reformer, whose contributions of conceptual thinking on education are still relevant today. Education develops the 3 H (Heart, Head, Hand), meaning that human beings must improve their spiritual attitudes and social attitudes, intellectual abilities, and skills. Pestalozzi also contributed thoughts on schools for democracy, teacher education programs, and humanism. This conception of Pestalozzi's thought, is very relevant for education in Indonesia today. The independent curriculum is colored by Pestalozzi's educational thinking, this is reflected in student-oriented education and the dimensions of the Pancasila Student Profile which instills human relationship with God, human relationship with man, and human relationship with the surrounding nature.